A comparative study of Filipino and Taiwanese students' mathematical communication skills based on Ill-structured tasks - De Vera, Jeffry, P. (College of Education, University of the Philippines Diliman, 2020)
This study analyzed and compared Filipino and Taiwanese students' mathematical communication skills (written, oral, and representational) based on ill-structured tasks. In addition, it analyzed how the curriculum, environment, technology, student learning opportunities, and teacher characteristics are associated with students' mathematical communication skills.